Making public the structure of the court. A comparative study and potentialities of court yearbooks and of their diffusion across the Holy Roman Empire and Central Europe during the 18th century.: - Hassler, Eric (Librosdelacorte.es, 2021)
The yearbooks published in court almanacs can be interpreted as a new type of publication that was born in the early eighteenth century. It represented the court in a novel manner and enabled the public to comprehend the court as an institution. Particularly common in the German-speaking world (the Holy Roman Empire and the Habsburg lands), these publications listed all the members of court’s personnel, department by department. These yearbooks represent a very important and attractive source for court studies: they not only allow a comparative and connected history based on the tables that the different courts published each year, but also a deepen study based on their symbolic and political dimension. Indeed, the almanacs constitute courts on paper form, and highlight the rationalization that this institution underwent during the Enlightenment.